Effect of silver on thermal e.m.f and electric resistance of La-Sr-Co-O ceramics - Kozlovskii, A.A.; Khirnyi, V.F.; Deineka, T.G.; Semenov, A.V.; Puzikov, V.M.; Mateychenko, P.V.; Finkel, V.A. (Functional Materials, 2008)
The effect of silver on thermal e.m.f and electric resistance of La₁₋ₓSrₓCoO₃-δ (x=0; 0.15; 0.35) ceramic samples prepared by solid phase synthesis has been demonstated. The thermoelectric characteristics of the ceramics become enchanced by the silves addition, the conductivity character remaining unchanged.